MENINGKATKAN PRESTASI BELAJAR SISWA TENTANG PERSAMAAN LINIER DAN PERTIDAKSAMAAN LINIER SATU VARIABEL BIDANG STUDI MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN STAD PADA SISWA KELAS VII.1 SMPN 2 TAMBUSAI - S., Sri Megawati (Edu Research, 2017)
This study aims to remind all the memory in the minds of students they have received. Teachers should be able to revive the memory so that it can improve student achievement. This research is action research, using action research model from Kemmis and Taggart in Sugiarti (1997), which is spiral from one to the next. Each cycle includes planning, action, observation, and reflection. The results showed that learning with STAD type learning model can improve student's learning achievement in every cycle, that is pre cycle 30%, cycle I 73,33% and cycle II 100% with KKM 70. Application of active learning method of STAD type learning model on material The subjects of linear equations and linear inequalities of one variable have a positive influence, that is can improve student learning pretation which is indicated by mean of student answer which states that student interested and interested with STAD model.